Empowering KWT Puspitasari through Maggot Utilization for Organic Waste Reduction in Semarang, indonesia - Suharini, Erni; Kurniawan, Edi; Saputro, Purnomo Adi; Al-hanif, Ervando Tommy; Rahayu, Endah Fitriani; Astuti, Eli Dwi; Nafi'ah, Khoirima; Syifauddin, Mohammad Syifauddin; Putri, Priyanti Handayani (Universitas Negeri Semarang, 2025)
Household organic waste has become an increasing problem in urban areas due to population growth and changing consumption patterns. Improperly managed organic waste may cause environmental and public health impacts. This community service program aimed to enhance the capacity of Kelompok Wanita Tani (KWT) Puspitasari in managing household organic waste through the cultivation of Black Soldier Fly (BSF) larvae. The method applied a participatory approach consisting of training sessions, demonstrations, hands-on practice, and mentoring, evaluated using a pretest–posttest design. The results indicated a significant improvement in participants’ knowledge, with the mean score increasing from 61.47 to 83.24 and the Wilcoxon test showing p = 0.001. In addition to cognitive improvement, participants demonstrated practical competence and commitment to continue maggot cultivation independently. The findings confirm that BSF cultivation represents an innovative, sustainable, and economically promising solution for community-based organic waste management.